Using social media platforms to improve communicative english proficiency among diploma students in Malaysian Polytechnics - Muhamad Affendi, Norliyana Bau; Ibrahim, Liyana (Jurnal Penyelidikan Sains Sosial, 2025)
This qualitative study explores diploma students' experiences and perceptions of using social media platforms to improve communicative English proficiency within a Malaysian polytechnic context. Despite extensive English instruction throughout their education, Malaysian polytechnic students often struggle to achieve effective communicative competence due to limited authentic practice opportunities. This research addresses the gap by examining how students leverage social media to enhance their English language skills and overcome linguistic barriers. Data were collected from eight diploma students using semi-structured interviews and analysed through thematic analysis. Findings reveal that social media platforms, including YouTube, Instagram, TikTok, and Reddit, provide accessible, flexible, and engaging environments for autonomous, self-directed language practice. Students strategically use different platforms to develop specific language skills, such as speaking, listening, reading, and writing, benefitting from real-time interactions and community engagement. Additionally, integrated technological tools like AI-driven language assistants and instant grammar correction significantly bolster students' confidence, promoting more frequent and effective language use. Despite these positive outcomes, potential distractions and inconsistent linguistic input highlight the necessity of educator guidance and structured integration into language curricula. This study contributes valuable insights to language education by highlighting practical strategies for leveraging social media to improve communicative English proficiency. The implications inform educators and policymakers aiming to optimize digital learning environments in polytechnic institutions.